Deep eutectic solvent and inorganic salt pretreatment of lignocellulosic biomass for improving xylose recovery - Loow, Yu-Loong; Wu, Ta Yeong; Yang, Ge Hoa; Ang, Lin Yang; New, Eng Kein; Siow, Lee Fong; Md. Jahim, Jamaliah; Mohammad, Abdul Wahab; Teoh, Wen Hui (Elsevier, 2018)
Deep eutectic solvents (DESs) have received considerable attention in recent years due to their low cost, low toxicity, and biodegradable properties. In this study, a sequential pretreatment comprising of a DES (choline chloride:urea in a ratio of 1:2) and divalent inorganic salt (CuCl 2 ) was evaluated, with the aim of recovering xylose from oil palm fronds (OPF). At a solid-to-liquid ratio of 1:10 (w/v), DES alone was ineffective in promoting xylose extraction from OPF. However, a combination of DES (120 °C, 4 h) and 0.4 mol/L of CuCl 2 (120 °C, 30 min) resulted in a pretreatment hydrolysate containing 14.76 g/L of xylose, remarkably yielding 25% more xylose than the CuCl 2 -only pretreatment (11.87 g/L). Characterization studies such as FE-SEM, BET, XRD, and FTIR confirmed the delignification of OPF when DES was implemented. Thus, the use of this integrated pretreatment system enabled xylose recoveries which were comparable with other traditional pretreatments.